Evaluation of antimicrobial photodynamic therapy and minimal intervention associated with deproteinisation in permanent teeth with molar incisor hypomineralisation: study protocol for a clinical, controlled, blinded trial - Ana Paula Taboada Sobral; Marcela Leticia Leal Gonçalves; Lara Jansiski Motta; Anna Carolina Ratto Tempestini Horliana; Kristianne Porta Santos Fernandes; Sandra Kalil Bussadori; Raquel Agnelli Mesquita Ferrari; Amanda Rafaelly Honório Mandetta; Carolina Carvalho Bortoletto; Renato Araujo Prates; Alessandro Melo Deana; Rita de Cássia Loiola Cordeiro; et al. (BMJ Open, 2023)
Introduction Molar incisor hypomineralisation (MIH) is a qualitative defect of enamel development that occurs in the mineralisation phase. MIH affects one or more permanent molars and, occasionally, permanent incisors. The aim of the proposed study is to evaluate the clinical effect of antimicrobial photodynamic therapy (aPDT) on permanent teeth with MIH through decontamination and sensitivity control.Methods and analysis Patients from 8 to 12 years of age with permanent molars will be randomly allocated to three groups. Group 1: selective chemical–mechanical removal of carious dentinal tissue around the walls of the cavity with Papacárie Duo and a curette followed by the application of aPDT and deproteinisation with Papacárie Duo; group 2: selective removal of carious dentinal tissue around the walls of the cavity with a curette, followed by the application of aPDT and deproteinisation with a 5% sodium hypochlorite solution; group 3: selective removal of carious dentinal tissue using a curette. The selected teeth must have a carious lesion in the dentin and posteruptive enamel breakdown on one or more surfaces with an indication for clinical restorative treatment. The teeth will subsequently be restored using a mixed technique with resin-modified glass ionomer cement and bulk-fill composite resin. The data will be submitted to descriptive statistical analysis. Associations with age and sex will be tested using either the χ2 test or Fisher’s exact test. Pearson’s correlation coefficients will be calculated to determine the strength of correlations between variables. Comparisons of the microbiological results (colony-forming units) will be performed using analysis of variance and the Kruskal-Wallis test. Kaplan-Meier survival analysis will be performed to assess the performance of the restorations.Ethics and dissemination This protocol has been approved by the Human Research Ethics Committee of Nove de Julho University (certificate number: 61027522.0.0000.5511/approval date: 23 August 2022). The findings will be published in a peer-reviewed journal.Trial registration number NCT05443035.